2006
DOI: 10.1021/jp062050h
|View full text |Cite
|
Sign up to set email alerts
|

Rotationally Resolved Electronic Spectra of 2- and 3-Methylanisole in the Gas Phase:  A Study of Methyl Group Internal Rotation

Abstract: Rotationally resolved fluorescence excitation spectra of several torsional bands in the S1 <-- S0 electronic spectra of 2-methylanisole (2MA) and 3-methylanisole (3MA) have been recorded in the collision-free environment of a molecular beam. Some of the bands can be fit with rigid rotor Hamiltonians; others exhibit perturbations produced by the coupling between the internal rotation of the methyl group and the overall rotation of the entire molecule. Analyses of these data show that 2MA and 3MA both have plana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
26
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 19 publications
5
26
0
Order By: Relevance
“…In 2006 Alvarez‐Valtierra et al. determined the rotational constants A =2.4900(1) GHz, B =1.5589(1) GHz, and C =0.9707(1) GHz, as well as a V 3 potential of 345 cm −1 for OMA by fluorescence spectroscopy . The rotational constants are not as accurate as in the present work, but they are in agreement with those deduced from our fit.…”
Section: Figuresupporting
confidence: 81%
See 2 more Smart Citations
“…In 2006 Alvarez‐Valtierra et al. determined the rotational constants A =2.4900(1) GHz, B =1.5589(1) GHz, and C =0.9707(1) GHz, as well as a V 3 potential of 345 cm −1 for OMA by fluorescence spectroscopy . The rotational constants are not as accurate as in the present work, but they are in agreement with those deduced from our fit.…”
Section: Figuresupporting
confidence: 81%
“…The barrier height of the ring methyl group has only been determined by Alvarez‐Valtierra et al. with fluorescence spectroscopy, where the authors found for the electronic ground state a V 3 potential of 345 cm −1 …”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…and with the anisole molecule which presents inertial defects very close to 3‐MP . This last point seems to indicate that the phenol group does not impact the planarity of the 3‐MP molecule contrary to the methyl internal rotor in methylanisole where the inertial defects are significantly larger compared to methoxyphenol ,…”
Section: Figurementioning
confidence: 85%
“…6 However, substitution of a second ring hydrogen atom with a methoxy group changes this situation dramatically. A recent study of 2-and 3-methylanisole 7 showed that the methyl group internal motions are significantly more rigid in one of the electronic states and less rigid in the other, with the corresponding barriers depending on the positions of the two groups relative to one another.…”
Section: Introductionmentioning
confidence: 99%